SDN resolve space-ground integrated network based on end side computing - Jinglin LI; Xiaolan WAN (Dianxin kexue)
There is a complex network structure of space-ground integrated network.And this kind of network has heterogeneous network,dynamic topology,intermittently connected node height exposure,and so on.There are many limitations in traditional SDN implementation.A method of SDN implement based on end side computing and a space-ground integrated network based on SDN were presented,which separated space network control and data,using the computing power of the communication terminal (mobile terminal and fixed ground backbone network),unloading the calculation of SDN controller in space-based plane,thus simplifying the data forwarding plane.A practical and effective verification method was also proposed.